Estimation of the Duration Model by Nonparametric Maximum Likelihood, Maximum Penalized Likelihood, and Probability Simulators - Huh, Keun; Sickles, Robin C. (The Review of Economics and Statistics, 1994)
Keun Huh, Robin C. Sickles, Estimation of the Duration Model by Nonparametric Maximum Likelihood, Maximum Penalized Likelihood, and Probability Simulators, The Review of Economics and Statistics, Vol. 76, No. 4 (Nov., 1994), pp. 683-694